2014
DOI: 10.1111/aos.12581
|View full text |Cite
|
Sign up to set email alerts
|

Early and exudative age‐related macular degeneration is associated with increased plasma levels of soluble TNF receptor II

Abstract: ABSTRACT.Purpose: We have recently identified homeostatic alterations in the circulating T cells of patients with age-related macular degeneration (AMD). In cultures of retinal pigment epithelial cells, we have demonstrated that T-cell-derived cytokines induced the upregulation of complement, chemokines and other proteins implicated in AMD pathogenesis. The purpose of this study was to test whether increased plasma levels of cytokines were present in patients with AMD. Methods: We conducted a case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
0
24
0
3
Order By: Relevance
“…Apart from Faber et al. () and Haas et al. () which used ICGA for retinal diagnosis, other studies did not employ ICGA for diagnosis and some even based retinal diagnosis solely on fundus photography (Klein et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from Faber et al. () and Haas et al. () which used ICGA for retinal diagnosis, other studies did not employ ICGA for diagnosis and some even based retinal diagnosis solely on fundus photography (Klein et al.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of quantifying the labile cytokine TNF‐ α , we quantified the soluble TNF‐R2, which has a longer half‐life and is a more stable measure of the average TNF‐ α level (Faber et al. ). Cytokines were quantified using the commercially available U‐PLEX Human Assays™ (U‐PLEX, Meso Scale Diagnostics, Rockville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…[58] Increased plasma level of soluble TNF-II was also found to be associated with AMD. [59] Lechner et al . have observed that circulating CD11b(+) cells and CD16 (hi) HLA-DR(−) neutrophils were found to be increased significantly in AMD patients when compared to controls.…”
Section: Circulating Biomarkers In Age-related Macular Degenerationmentioning
confidence: 99%
“…; Faber et al. ; Haas et al. ), but whether these changes undergo change with time remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%